The Financial Structure and Performance of Philippine Credit Cooperatives - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 1994)
The Philippine credit cooperatives have grown in financial resources and membership over the last three decades. These cooperatives are self-reliant and self-sustaining. This paper is an attempt to assess the importance and potential impact of any further sectoral development and to identify development intervention that will lead to stronger credit cooperative financial system. It also formulates policy recommendations that support credit cooperative sector as a viable mechanism for a sustainable Philippine credit system.
Keywords: 330; rate of return; financial liquidity; credit unions; equity; credit cooperative; financial services; financial stabilization; capital adequacy; asset quality